Polymorphic forms of bendamustine hydrochloride: crystal structure, thermal properties and stability at ambient conditions - Gaztañaga, Pablo Ernesto (2019)
Crystallographic, thermal and stability analyses are presented of three different anhydrated forms of bendamustine hydrochloride [(I), (III) and (IV)] and a fourth, monohydrated one (II). Since form (I) presents the higher melting point and the higher heat of fusion, according to the 'heat of fusion' rule it should be the most stable in thermodynamic terms [Burger & Ramberger (1979). Mikrochim. Acta, 72, 259-271], though it is unstable in high-humidity conditions. The monohydrate structure (II), in turn, dehydrates by heating and topotactically transform into anhydrate (III). This latter form appears as less stable than anhydrate (I), to which it is linked via a monotropic relationship. For these three different forms, the crystal structure has been determined by single crystal X-ray diffraction. The crystal structures and molecular conformations of forms (II) and (III) are quite similar, as expected from the topotactic transformation linking them; furthermore, under high-humidity conditions, form (III) shows changes compatible with a transformation into form (II) within 24 h. The crystal structure of form (I) is different from the other two. The remaining polymorphic form (IV) could only be obtained as a powder, from which its crystalline structure could not be determined. The relative thermodynamic stability of the different crystalline forms was determined by differential scanning calorimetry and thermogravimetrical studies, and their stability under different humidity conditions analysed.